2022
DOI: 10.5455/javar.2022.i630
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of seahorse (Hippocampus comes L.) extracts originating from culture and nature in Pesawaran, Lampung, Indonesia

Abstract: Objective: Indonesia is an archipelagic country with a mega biodiversity, among others, in the marine area. Seahorses (Hippocampus spp.) are a marine fish known to have biocompounds used in traditional medicine “Jamu,” such as Hippocampus comes L. (HCL). The present study aims to analyze and compare the chemical contents of cultured seahorse (CS) and natural seahorse (NS) extracts. Materials and Methods: The CS and NS were identified morphometrically. After freeze-drying, the seahorses were ground into powder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Our study, however, provides a holistic nutritional evaluation by analyzing both amino acids and fatty acids in multiple species, highlighting interspecies and gender-specific variations. The study on Hippocampus comes compared cultured versus wild specimens [ 36 ], whereas our research does not limit the comparison to cultured and wild but rather focuses on the inherent biochemical differences among species. Additionally, while the investigation into marine amphipods as an alternative feed for Hippocampus erectus examined dietary effects on a single species [ 18 ], our study's broader species range offers foundational data for future studies on diet and nutrition across different seahorse species.…”
Section: Discussionmentioning
confidence: 99%
“…Our study, however, provides a holistic nutritional evaluation by analyzing both amino acids and fatty acids in multiple species, highlighting interspecies and gender-specific variations. The study on Hippocampus comes compared cultured versus wild specimens [ 36 ], whereas our research does not limit the comparison to cultured and wild but rather focuses on the inherent biochemical differences among species. Additionally, while the investigation into marine amphipods as an alternative feed for Hippocampus erectus examined dietary effects on a single species [ 18 ], our study's broader species range offers foundational data for future studies on diet and nutrition across different seahorse species.…”
Section: Discussionmentioning
confidence: 99%
“…The content in SE may play a role in spermatogenesis. In another study, we reported the biocompound in SE were alkaloids, steroid glycosides, triterpenoids, and amino acids, with L-Arginine and Glycine as the two highest amino acids [ 22 ]. The amino acids are used in Mitogen-Activated Protein Kinase, which increases the expression enzyme Prolyl Endopeptidase in the rat testes, which is regulated by spermatogenesis in mammals [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, we found the highest amino acids are L-Arginine and Glycine. L-Arginine is a non-essential amino acid which is a precursor of NO [ 25 ] and is widely found in seafood and acts as a precursor for the synthesis of putrescine, spermidine, and spermine which affect sperm motility [ 22 ]. Indeed, Glycine is one of the homopolymer amino acids as a steroid receptor that affects the androgen receptor involving interactions with Deoxyribonucleic Acid (DNA) and protein that affect the transcriptional activity of androgen receptors [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is sweet in taste and gently considered warm to human body. The Chinese Pharmacopeia stipulates that the dried body of three‐spot seahorse ( H. trimaculatus ) can be used as medicine and studies suggest that seahorses have ethnopharmacological characteristics, such as fertility, antioxidants, and anti‐fatigue (Liao et al., 2017 ; Mundijo, Midoen, et al., 2022 ; Mundijo, Suyatna, et al., 2022 ; Jiang et al., 2014 ). In the “Compendium of Materia Medica,” it is recorded that the seahorse has aphrodisiac effect (Xu et al., 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…This effect mainly due to alkaline protease hydrolysate (ALC) and pepsin hydrolysate (PEP) stimulating the proliferation of mouse Leydig cells (testosterone hormone is mainly secreted and proliferated by these cells), which increases serum testosterone levels. As a result, the diverse pharmacological activities of the seahorse make it a research hotspot recently (Mundijo et al., 2023 ; Mundijo, Midoen, et al., 2022 ; Mundijo, Suyatna, et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%